Multibody dynamic analysis of lightning protection systems for modern wind turbines - Godson, Ikhazuangbe Ivbuobe (2021)
Modern wind turbines are increasing in size due to higher megawatt, reaching height of about 220 m with blade as long as 80 m moving with a tip velocity of 60-80 m/s. They are sometimes located offshore for better wind condition, bringing them closer to lightning, and the blade is mostly affected when hit. When lightning attaches to the blade surface instead of the air-terminal, the blade and sometimes the entire wind turbine may be destroyed resulting in downtimes, loss of wind turbine, expensive cost of repair and can cause some power companies to shut down and dismantle. Damage incidences has been recorded as well as increased insurance claims. In the past decades, lightning protection issues were well addressed for static objects and Lightning Protection Systems (LPS) are usually installed on modern wind turbines by applying the Electro Geometric Model (EGM) methods. Recently, these methods are invalidated and according to IEC 61400-24, the EGMs are no longer appropriate for large wind turbine blades. Lightning can either be downward initiated or upward initiated. In the presence of a thundercloud, tall wind turbines are increasingly subjected to upward lightning attachment triggered by the wind turbine itself. Lightning strike frequency, point of lightning attachment and lightning protection systems has been evaluated based on downward initiated lightning. However, these might not be effective for upward lightning. Research has shown that the maximum electric field strength distributed on the surface of the wind turbine and the surrounding air is very important in determining the point of inception of upward leader and would help in improving lightning protection systems. In contrast to static objects, maximum electric field strength required for the inception of upward leader from wind turbine changes majorly due to blade rotation and certain blade conditions such as; polluted blade condition, varying receptor sizes, receptor positions and type of protection method.